Community, Comunidad, Collectives and Neoliberal Political Decentralization in Peru - Vincent, Susan (Anthropologica, 2012)
Community building is both derided as the product of neoliberal regionalization and extolled as its alternative. The Peruvian community of Allpachico demonstrates that these two facets are linked. I show how forms of association have adapted to changing economic patterns over the past 100 years. Thus, the comunidad campesina, established to support small-scale agriculture, now offers unpaid peasant labour to state projects that both sustain cheap wage rates and produce infrastructure of prime interest to migrants. However, these projects also en sure the ongoing viability of the community, which relies on complex relationships between peasants, pensioners and mi grant workers.